2022
DOI: 10.1108/baj-08-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

Privacy concerns and avoidance behaviour towards data-driven online behavioural advertising

Abstract: PurposeWith the developments of the digital era and considerable developments in ICT, advertisers are leveraging data-driven forms of online advertising to target consumers individually. The present study integrates privacy concerns with the constructs from the persuasion knowledge model to investigate consumer avoidance of online behavioural advertising (OBA).Design/methodology/approachThe study employed an online survey method for data collection using a sample size of 345. Reliability and validity of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Prior work shows that in the case of behavioral advertising, persuasion knowledge affects privacy risk perceptions. While existing research shows that if people know that they are exposed to personalized messages, this affects privacy risks [54] or that users even feel that these messages are intrusive or creepy, our results did not align with this [23,53]. Moreover, we would like to point out that our result aligns with the novel work by Dobber and colleagues, who also did not find a relationship between exposure to transparency information and users' privacy concerns [36].…”
Section: Plos Onecontrasting
confidence: 91%
See 1 more Smart Citation
“…Prior work shows that in the case of behavioral advertising, persuasion knowledge affects privacy risk perceptions. While existing research shows that if people know that they are exposed to personalized messages, this affects privacy risks [54] or that users even feel that these messages are intrusive or creepy, our results did not align with this [23,53]. Moreover, we would like to point out that our result aligns with the novel work by Dobber and colleagues, who also did not find a relationship between exposure to transparency information and users' privacy concerns [36].…”
Section: Plos Onecontrasting
confidence: 91%
“…Recent work validating a scale on perceived surveillance concerning personalization effects found that users experience creepiness, concerns about surveillance, perceptions of privacy risks overall, and privacy concerns [53]. In addition, other work found that in the case of data-driven OBA, persuasion knowledge, on which the concept of targeting knowledge is built, positively affects privacy risks, which could be considered as the cost side of the privacy calculus theory [54]. Dobber and colleagues [13] found that privacy concerns regarding PMT lead to more negative attitudes towards the technique and reversibly a higher attitude towards the technique leads to a decrease in privacy concerns.…”
Section: Privacy Concernsmentioning
confidence: 99%